Loading...

The expression is 33.

3/5 = .6

2(2x + 3)

6 (3+10)

The expression 9+5 is equivalent.

69 is an equivalent expression.

4(3 + 2x)(-3 + 2x) ¯_(ツ)_/¯

486 - 9 + 6 + 3 + 2 = 488

Yes, -6+x is the same as x-6.

-21

6

0

The expression 1000^(1/3) is equivalent.

10

166 = 16,777,216

It is: 63 to 27 is equivalent 7 to 3

3x + 3x + 3x = 3* (3x) = 9x

Equivalent ExpressionDefinition of Equivalent ExpressionTwo algebraic expressions are said to be equivalent if their values obtained by substituting the values of the variables are same.More about Equivalent ExpressionTo symbolize equivalent expressions an equality (=) sign is used.Examples of Equivalent Expression3(x + 3) and 3x + 9 are equivalent expressions, because the value of both the expressions remains same for any value of x. For instance, for x = 4, 3(x + 3) = 3(4 + 3) = 21 and 3(x + 9) = 3 × 4 + 9( x + 3) = 21.The expressions 6(x2 + y + 2) and 6x2 + 6y + 12 are equivalent expressions and can also be written as 6(x2 + y + 2) = 6x2 + 6y + 12.Solved Example on Equivalent ExpressionChoose an expression that is equivalent to the expression 2n + 7(3 + n).Choices:A. 9n + 21B. -9n + 21C. -9n - 21D. n + 21Correct Answer: ASolution:Step 1: 2n + 7(3 + n) [Original expression.]Step 2: = 2n + 7(3) + 7(n) [Use the distributive property.]Step 3: = 2n + 21 + 7n [Multiply.]Step 4: = 2n + 7n + 21 [Use the commutative property.]Step 5: = 9n + 21 [Combine like terms.]well....in a totally inataquitly way...theotorical...e=mc2

3/4

-14

10m + 3

17 + 6 + m

Radical (3x) = radical(x) * radical(3).

Equivalent ExpressionDefinition of Equivalent ExpressionTwo algebraic expressions are said to be equivalent if their values obtained by substituting the values of the variables are same.More about Equivalent ExpressionTo symbolize equivalent expressions an equality (=) sign is used.Examples of Equivalent Expression3(x + 3) and 3x + 9 are equivalent expressions, because the value of both the expressions remains same for any value of x. For instance, for x = 4, 3(x + 3) = 3(4 + 3) = 21 and 3(x + 9) = 3 Ã— 4 + 9( x + 3) = 21.The expressions 6(x2 + y + 2) and 6x2 + 6y + 12 are equivalent expressions and can also be written as 6(x2 + y + 2) = 6x2 + 6y + 12.Solved Example on Equivalent ExpressionChoose an expression that is equivalent to the expression 2n + 7(3 + n).Choices:A. 9n + 21B. -9n + 21C. -9n - 21D. n + 21Correct Answer: ASolution:Step 1: 2n + 7(3 + n) [Original expression.]Step 2: = 2n + 7(3) + 7(n) [Use the distributive Definition_for_Equivalent_Expressions.]Step 3: = 2n + 21 + 7n [Multiply.]Step 4: = 2n + 7n + 21 [Use the commutative property.]Step 5: = 9n + 21 [Combine like terms.]

360/540 is equivalent.